Article 24C Paragraph 1 of the 1945 Constitution of the Republic of Indonesia: History and Critical Analysis of Disputes on the Authority of State Institutions - Demas Brian Wicaksono (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2021)
In simple terms, the ratio legis can be interpreted as the reason why there is a provision in the law. Article 24C paragraph (1) of the 1945 Constitution of the Republic of Indonesia determines the authority possessed by the Constitutional Court, paragraph (1) reads: The Constitutional Court has the authority to adjudicate at the first and final levels whose decisions are final to examine laws against the Constitution, decide disputes over authority a state institution whose authority is granted by the Constitution, decides on the dissolution of political parties, and decides on disputes regarding the results of general elections. The limiting provisions of Article 24C paragraph (1) seem to close the scope for expanding the Constitutional Court authority to decide disputes over the authority of independent state institutions. Meanwhile, this is a state requirement. This research uses a statutory approach with a descriptive analysis method. The conclusions obtained are: 1) it is not possible that a state institution that has supervisory authority has conflict with other legal institutions; 2) there are state institutions whose authorities are regulated by law and have the potential for authority disputes, but are resolved through the executive agency; 3) there is the authority of state institutions that have the potential for conflict of authority but there are no rules for resolving them.